LAYANAN BIMBINGAN DAN KONSELING DALAM PENGENDALIAN EMOSI SISWA SEKOLAH DASAR - Regina Sipayung; Sinulingga, Kevin; Hotma Sitanggang; Siska Sihombing; Yulinda Sitepu; Olivia Perangin-angin; Hadasya Simanjuntak; Lierfin Simanullang; Gita Sembiring; Nia Sembiring; Gio Van Rio (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of guidance and counseling services on the emotional regulation of elementary school students at SD Negeri 030317 Gunung Sayang. The research employed a quantitative approach using a correlational design with simple linear regression analysis. The population consisted of fourth-, fifth-, and sixth-grade students, with a total sample of 48 students selected using the total sampling technique. Data were collected through questionnaires measuring guidance and counseling services and students' emotional regulation. The data were analyzed using descriptive and inferential statistics with the assistance of IBM SPSS Statistics version 26. The descriptive analysis showed that the mean score of guidance and counseling services was 84.38, indicating a high category, while the mean score of students' emotional regulation was 82.71, indicating a good category. The prerequisite tests confirmed that the data were normally distributed and that the relationship between variables was linear. Hypothesis testing using simple linear regression produced a significance value of 0.000 (p < 0.05) with the regression equation Y = 28.642 + 0.641X, indicating that guidance and counseling services had a positive and significant effect on students' emotional regulation. The coefficient of determination (R² = 0.428) revealed that guidance and counseling services contributed 42.8% to students' emotional regulation, while the remaining 57.2% was influenced by other factors. Therefore, guidance and counseling services play an important role in developing students' emotional regulation and supporting their social and emotional development in elementary schools.